ТАЛАБАЛАРДА ПОЗИТИВ ДУНЁҚАРАШНИ ШАКЛЛАНТИРИШ ОМИЛЛАРИ - Якубова, Ш.Э. (SCIENCE and SOCIETY, 2023)
This article highlights the didactic aspects of creating a positive worldview in students based on the pedagogical teachings of Eastern thinkers.
Keywords: Alisher Navoi; Zahriddin Muhammad Babur; Jalaluddin Rumi; creativity; positive interpersonal relationships; experience; devotion; patriotism; friendship; tolerance; spiritual world